Clinical experience of extracorporeal shock wave lithotripsy in treatment of proximal ureteral stones employing the recent Richard Wolf, PiezoLith 3000Plus at Al-Azhar University Hospital, Assiut branch - Gamal A. Morsi; Hazem A. Dief; Deyaa E.S. Ramadan (Al-Azhar Assiut Medical Journal)
Background and aim Urological stones are prevalent conditions that impact many individuals globally and put significant stress on the healthcare system. The study aims to assess the efficacy of shock wave lithotherapy as a therapeutic for proximal ureteral stones regarding patient and stone factors such as BMI, skin-to-stone distance (SSD), stone size, density, radio-opacity, and other factors, identify the group of patients for whom this treatment can be administered most effectively to achieve complete stone-free (SF) status. Patients and methods The study was prospective research and included 50 patients. It was conducted from October 2022 to May 2023 at the Alazher University Hospital Assiut branch. Results The success of shock wave lithotherapy in upper ureteric stones may be recognized through identifying elements like patient BMI, age, SSD, and calculus density. Considerable variance existed among SF status, SSD, BMI, stone size, stone density, ureteral stenting, stone radio-opacity, and frequency rate (P=0.025, 0.0281, 0.0281, 0.0232, 0.057, 0.053, 0.054, respectively), but there was no significant relation between SF status, age, sex, total number. Of shock waves in a single session, or degree of HUN (P=0.0651, 0.067, 0.063, 0.065). Conclusion The overall success rate is 80%, with 20% of cases failing. The PiezoLith 3000Plus device, developed by Richard Wolf, is highly effective in treating proximal ureteral stones.